(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Margarita A. Khatlamadzhiyan, Anna V. Lenets (Rostov-on-Don, Russian Federation) The article describes the nonverbal aspect of realization of the false statements by defining canals of nonverbal cooperation. 275 dialogical fragments of the German fictional text were analyzed. The article examines detailed study of visual, acoustic and tactile markers in the act of lie realization. Research results demonstrate that visual signs of nonverbal semiotics are prevalent by the lie producing. Key words: nonverbal means, false statements, kinesic, acoustic, tactile components. DOI 10.23683/1995-0640-2018-1-110-116